TRADISI MERANTAU DALAM “LELAKI DAN TANGKAI SAPU” (Tradition of Wandering in “Lelaki dan Tangkai Sapu”) - NFN Marlina (Balai Bahasa Sulawesi Selatan, 2018)
The poem “Lelaki dan Tangkai Sapu” (Man and the Broomstick) by Iyut Fitra is story of a man named Malin, starting from the birth, undergoing childhood and adolescence like the Minangkabau children in general. Reciting Holy Quran and also staying overnight at Surau. In addition, Malin also learned martial arts at the arena and sat in Lapau like other Minangkabau men. This research examined the wandering culture contained in the poem “Lelaki dan Tangkai Sapu” by Iyut Fitra. Wandering is an effort to navigate life through a variety of experiences, breadth science to achieve success. The tradition of wandering for the Minangkabau community still persists until now. How does Iyut Fitra describe men and women in her poems? How is the poet’s view concerning the tradition of wandering in Minangkabau culture? Is the culture of wandering always positive to the Minangkabau people? Through the sociological approach of literature, an overview of this will be obtained; while for analyzing each poem the methodology of desciption is used so that it is revealed that men in the Minangkabau community are destined to wander. However, Iyut Fitra has a different view than other Minangkabau people in general concerning the culture of wandering.AbstrakPuisi “Lelaki dan Tangkai Sapu” karya Iyut Fitra bercerita tentang seorang laki-laki bernama Malin,mulai dari lahir, menjalani masakanak-kanak dan remaja seperti anak-anak Minangkabau pada umumnya. Iabelajar mengaji di surau sekaligus tidur dan bermalam di surau. Malin juga belajar ilmu bela diri di gelanggang serta duduk di lapau seperti laki-laki Minangkabau lainnya. Penelitian ini mengkaji budaya merantau yang terdapat di dalam puisi “Lelaki dan Tangkai Sapu” karya Iyut Fitra. Merantau merupakan suatu upaya untuk mengarungi kehidupan melalui keragaman pengalaman, keluasan ilmu pengetahuan untuk meraih kesuksesan.Tradisi merantau pada masyarakat Minangkabau masih bertahan hingga saat sekarang.Lalu bagaimanakah Iyut Fitra menggambarkan lelaki dan rantau di dalam puisipuisinya? Bagaimanakah pandangan penyair ini tentang tradisi merantau dalam budaya Minangkabau? Apakah budaya merantau selalu bernilai positif bagi masyarakat Minangkabau? Melalui pendekatan sosiologis sastra akan diperoleh gambaran tentang hal ini; sementara untuk mengkaji masing-masing puisi digunakan metodologi deskripsi analisis sehingga terkuaklah bahwa lelaki di dalam masyarakat Minangkabau memang ditakdirkan untuk merantau. Namun, Iyut Fitra memiliki pandangan yang berbeda dengan masyarakat Minangkabau pada umumnya tentang budaya merantau.